Answer:
A: factor the equation to (x -3)(x +4) = 0
B: solutions are x=-4, x=3
Step-by-step explanation:
A: Santos has the equation in standard form. Several options for solution are available: graphing (see attached), completing the square, factoring, using the quadratic formula. I find factoring to get to the solution most directly. The other methods work just as well.
To factor the equation, Santos needs to find two factors of -12 that have a sum of +1. Those would be +4 and -3. Putting these numbers into the binomial factors, Santos would have ...
(x +4)(x -3) = 0
__
B: The values of x that make the factors zero are ...
x = -4, x = 3